Chromatin remodeling and control of cell proliferation by progestins via cross talk of progesterone receptor with the estrogen receptors and kinase signaling pathways - Vicent, Guillermo P. (2006)
Transcription from the mouse mammary tumor virus (MMTV) promoter can be induced by glucocorticoids or progestins. Progesterone treatment of cultured cells carrying an integrated single copy of an MMTV transgene leads to recruitment of progesterone receptor (PR), SWI/SNF, and SNF2h-related complexes to MMTV promoter. Recruitment is accompanied by selective displacement of histones H2A and H2B from the nucleosome B. In nucleosomes assembled on promoter sequences, SWI/SNF displaces histones H2A and H2B from MMTV nucleosome B, but not from other MMTV nucleosomes or from an rDNA promoter nucleosome. Thus, the outcome of nucleosome remodeling by purified SWI/SNF depends on the DNA sequence. On the other hand, 5 min after hormone treatment, the cytoplasmic signaling cascade Src/Ras/Erk is activated via an interaction of PR with the estrogen receptor, which activates Src. As a consequence of Erk activation PR is phosphorylated, Msk1 is activated, and a ternary complex PR-Erk-Msk1 is recruited to MMTV nucleosome B. Msk1 phosphorylates H3 at serine 10, which is followed by acetylation at lysine 14, displacement of HP1gamma, and recruitment of Brg1, PCAF, and RNA polymerase II. Blocking Erk activation or Msk1 activity prevents induction of the MMTV transgene. Thus, the rapid nongenomic effects of progestins are essential for their transcriptional effects on certain progestin target genes. In rat endometrial stromal cells, picomolar concentrations of progestins trigger the cross talk of PR with ERbeta that activates the Erk and Akt kinase pathways leading to cell proliferation in the absence of direct transcriptional effects of the ligand-activated PR. Thus, depending on the cellular context rapid kinase activation and transcriptional effect play different roles in the physiological response to progestins.